Do Environmental Investments for Production Pay Off? A Study in Vietnam's Small and Medium-sized Enterprises - Nguyen, Tung Nhu; Goh Guan Gan, Gerald; Parvin Hosseini, Seyed Mehrshad (International Journal of Energy Economics and Policy, 2021)
Environmental preservation is one of the top priorities of the United Nations' sustainable development goals (SDGs). Environmental investments for production not only demonstrate corporate commitment to these universally accepted goals but also create a safe and healthy work environment for workers. However, previous studies have shown positive and negative effects of environmental investments for production on firm-level labor productivity. This paper aims to investigate how environmental investments for production influence labor productivity in Vietnamese manufacturing small and medium-sized enterprises (SMEs). An analysis of 1,176 valid responses by business owners or managers in Vietnam's manufacturing SMEs shows that environmental investment costs are positively associated with labor productivity. The results also confirm that labor productivity is affected by capital intensity, firm size and firm age. We realize that the impact of environmental investments for production on labor productivity is more advantageous in SMEs with higher capital intensity. Based on these research findings, SME-supporting policies should enable SMEs to get more capital to implement workplace environment investments, which lead to labor productivity and contribute to pollution control. Keywords: environmental investments, labor productivity, small and medium-sized enterprises, Vietnam JEL Classifications: Q01, Q53, D24, D25 DOI: https://doi.org/10.32479/ijeep.11836